1998
DOI: 10.1210/en.139.12.4991
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral-Type Benzodiazepine Receptor Function in Cholesterol Transport. Identification of a Putative Cholesterol Recognition/Interaction Amino Acid Sequence and Consensus Pattern

Abstract: In steroid-synthesizing cells, like the MA-10 mouse tumor Leydig cells, the peripheral-type benzodiazepine receptor (PBR) is an outer mitochondrial membrane protein involved in the regulation of cholesterol transport from the outer to the inner mitochondrial membrane, the rate-determining step in steroid biosynthesis. Expression of PBR in Escherichia coli DE3 cells, which have no PBR, no cholesterol, and do not make steroids, induced the ability to take up cholesterol in a time-dependent, temperature-sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
386
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(394 citation statements)
references
References 0 publications
7
386
0
1
Order By: Relevance
“…We have shown that LtxA binds specifically to cholesterol-containing membranes in a unique mechanism with a strong cholesterol-dependent dissociation rate but a cholesterol-independent association rate (Fig. 2) ), were identified as potential cholesterol binding sites, based upon the CRAC motif, (L/V)X 1-5 YX 1-5 (R/K) (60,61). Although both sites are juxtaposed to the LtxA hydrophobic domain, the requirements for a CRAC motif are quite flexible, and therefore, not all predicted CRAC sites bind cholesterol or possess an in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that LtxA binds specifically to cholesterol-containing membranes in a unique mechanism with a strong cholesterol-dependent dissociation rate but a cholesterol-independent association rate (Fig. 2) ), were identified as potential cholesterol binding sites, based upon the CRAC motif, (L/V)X 1-5 YX 1-5 (R/K) (60,61). Although both sites are juxtaposed to the LtxA hydrophobic domain, the requirements for a CRAC motif are quite flexible, and therefore, not all predicted CRAC sites bind cholesterol or possess an in vivo function.…”
Section: Discussionmentioning
confidence: 99%
“…The potential of camel milk lactoferrin for its ability to inhibit the proliferation of the colon cancer cell line has been reported [42]. The concentration of lysozyme, lactoferrin and immunoglobulins in camel milk is higher than in bovine or buffalo milk [30,68]. The antimicrobial activity of these molecules is, however, lost in camel milk after heat treatment at 100°C for 30 min [25].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…The hypocholesterolemia mechanism of camel milk is still unclear, but different hypotheses have been proposed, including: interaction between bioactive peptides derived from camel milk proteins and cholesterol, which result in cholesterol reduction [68], and the presence of orotic acid in camel milk which is thought to be responsible for lowering cholesterol level in human subjects [17] and in rats [96].…”
Section: Antiatherosclerosis Propertymentioning
confidence: 99%
“…With the critical residues that affect cholesterol sensitivity being primarily non-polar aliphatic, the cholesterol-binding regions that we have identified differ from both the CRAC and the CCM cholesterol binding motifs, which include an aromatic residue and a positively charged residue in addition to a non-polar aliphatic residue. Specifically, the CRAC motif is -(L/V)X 1-5 YX 1-5 (R/K)-, where X 1-5 represents 1-5 residues of any amino acid (28,29). The CCM cholesterol binding motif includes sites on adjacent helices: (W/Y)(I/V/L)(K/R) on one helix and (F/Y/R) on the second helix (32).…”
Section: Figurementioning
confidence: 99%
“…Recent studies have shown that a well known cholesterol binding motif, the cholesterol recognition amino acid consensus (CRAC) motif (28,29), is found in TRPV1 channels (21) and in BK channels (30), representing putative cholesterol binding sites. CRAC motifs are also found in several types of AChR, but it has been suggested that it is not the CRAC itself but rather its inverted sequence, CARC, that may be responsible for cholesterol interactions with AChR (31).…”
mentioning
confidence: 99%